Removal and killing of multispecies endodontic biofilms by N-acetylcysteine - Young-Suk Choi (Brazilian Journal of Microbiology)
ABSTRACT Removal of bacterial biofilm from the root canal system is essential for the management of endodontic disease. Here we evaluated the antibacterial effect of N-acetylcysteine (NAC), a potent antioxidant and mucolytic agent, against mature multispecies endodontic biofilms consisting of Actinomyces naeslundii, Lactobacillus salivarius, Streptococcus mutans and Enterococcus faecalis on sterile human dentin blocks. The biofilms were exposed to NAC (25, 50 and 100 mg/mL), saturated calcium hydroxide or 2% chlorhexidine solution for 7 days, then examined by scanning electron microscopy. The biofilm viability was measured by viable cell counts and ATP-bioluminescence assay. NAC showed greater efficacy in biofilm cell removal and killing than the other root canal medicaments. Furthermore, 100 mg/mL NAC disrupted the mature multispecies endodontic biofilms completely. These results demonstrate the potential use of NAC in root canal treatment.